Design and evaluation of the crimping of a hooked self-expandable caval valve stent for the treatment of tricuspid regurgitation. Issue 5 (4th April 2019) - Praveen Kumar, Gideon; Liang Leo, Hwa; Cui, Fangsen
Abstract: To design a hooked self-expandable caval valve stent and determine the best crimping scenario for its percutaneous implantation in the Superior and Inferior Vena Cava (SVC & IVC) for the treatment of tricuspid regurgitation (TR). A hooked, Nitinol based stent design was modeled using SOLIDWORKS and finite element analysis (FEA) was carried out using ABAQUS. The Nitinol material used in this study was modeled in ABAQUS as superelastic-plastic. Two cases were simulated. In case A, the stent model was crimped to 18 F by compressing the stent main body and then: (i) bending both the proximal and distal hooks; (ii) straightening the proximal hooks and bending the distal hooks. In case B, the stent model was crimped to 18 F by: (i) bending the proximal and distal hooks and then compressing the stent main body; (ii) straightening the proximal hooks and bending the distal hooks and then compressing the stent main body. The maximum strain after crimping was used to evaluate the best crimping scenario. Hook straightening produced strains of 10.7% and 10.96% as opposed to 12.6% and 13.0% produced by hook bending. From comparison of results of both cases simulated, it was found that straightening the hooks gave lower strain and thus was the best crimping procedure. The analysis performed in this paper may help understand the critical issue of crimpability of the new stent design. The best crimping scenario can be found based on finite element modeling and simulation. Identifying the best crimping way will also help the design team to optimize the delivery system that will eventually be used to deploy this caval valve stent.